Por um novo modelo de formação e aperfeiçoamento da formação de agentes de segurança penitenciária inspirado na experiência da Acadepen de 1997 a 1.999 - Kunugi, Rui Yoshio (2016)
This work is born from the researcher's experience within the prison system as a professor of criminology 1997-1999 in various prisons in the state of São Paulo, teaching for prison guards, commonly called jailers. From his observation sharp difference among their students and others, given that the training provided by the Penitentiary Academy at the time was planned for the prison model was modified with a new mindset for these professionals. For various reasons, the group of teachers was extinguished and the training course for prison guards was destroyed, and thus the formation of the new agent became ill, hurting himself and the social group they belong to. Faced with so many problems arising from the expansion of prisons in Sao Paulo, and the huge increase of prisoners within the São Paulo prisons, it had to rescue the technical course on prison security officer training from 1997 to 1999 and from this experience design, the final conclusions some targets in the emergence of new business resulting from this experience, as well as the formation of criminologists and some goals to be met in prison